Artificial intelligence and IoT for water saving in agriculture: A systematic review - Lucio Colizzi; Giovanni Dimauro; Emanuela Guerriero; Nunzia Lomonte (Smart Agricultural Technology)
Smart irrigation and fertigation offer three key benefits: sustainability through water conservation, increased productivity via targeted fertigation that activates only when necessary, and enhanced efficiency through remote control and high-precision sensors. This document presents a comprehensive review of the most significant innovations in this field over the past five years. The main components analyzed include sensors for monitoring and data acquisition, protocols and Internet of Things architectures for network management, and Artificial Intelligence models for decision-making and predictions. This study followed the PRISMA 2020 protocol and made use of data from Scopus and Web of Science. A total of 130 articles were identified as relevant and examined in detail. Alongside summarizing the collected articles, the review also includes an analysis of proposed future developments to inspire new research and drive innovation in this domain.